CRITICAL THINKING IN ELT: INDONESIAN TEACHERS’ UNDERSTANDING AND PRACTICE TEN YEARS DOWN THE TRACK - Maya Defianty; Kate Wilson (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
ABSTRACTIt has been over a decade since the Ministry of Education and Culture in Indonesia mandated teachers to foster critical thinking; however, studies document that in Indonesia, students’ critical thinking still lags behind other countries. This condition led us to investigate teachers’ understanding of critical thinking as they hold the central role in promoting it. This qualitative research survey involved 64 English language teachers who had signed up for a webinar about critical thinking. The respondents varied in terms of gender, educational background, and teaching experience. The questionnaire was distributed online, and their participation in filling out the questionnaire was voluntary. Questions were divided into two categories: the respondents’ demographic data, including gender, educational background, and teaching context. The second category focused on teachers’ understanding of critical thinking and its implementation in the classroom context. The study found that teachers do not yet have comprehensive knowledge about critical thinking, and this is reflected in their teaching practice and assessment of students’ critical thinking. Interestingly, the study revealed that only a few teachers realized that their difficulties in promoting critical thinking might derive from their limited understanding about the notion.ABSTRAKSudah lebih dari satu dekade sejak Kementerian Pendidikan dan Kebudayaan di Indonesia mengamanatkan guru untuk meningkatkan kemampuan berpikir kritis; namun, beberapa studi mendokumentasikan bahwa di Indonesia, tingkat kemampuan berpikir kritis siswa masih tertinggal dari negara lain. Kondisi ini mendorong Kami untuk meneliti pemahaman guru tentang berpikir kritis mengingat guru memegang peran penting sentral dalam mempromosikannya. Survei penelitian kualitatif ini melibatkan 64 guru bahasa Inggris yang telah mendaftar untuk webinar tentang berpikir kritis. Responden bervariasi dalam hal jenis kelamin, latar belakang pendidikan, dan pengalaman mengajar. Kuesioner disebarkan secara online, dan partisipasi mereka dalam mengisi kuesioner bersifat sukarela. Pertanyaan dibagi menjadi dua kategori: data demografi responden, termasuk jenis kelamin, latar belakang pendidikan, dan konteks pengajaran. Kategori kedua berfokus pada pemahaman guru tentang berpikir kritis dan implementasinya dalam konteks kelas. Studi ini menemukan bahwa guru belum memiliki pengetahuan yang komprehensif tentang berpikir kritis, dan hal ini tercermin dalam praktik mengajar mereka serta dalam menilai kemampuan berpikir kritis siswa. Salah satu temuan menarik dari penelitian ini adalah hanya sedikit guru yang menyadari bahwa kesulitan mereka dalam mempromosikan berpikir kritis pada siswa kemungkinan besar dikarenakan pemahaman mereka yang terbatas tentang konsep berpikir kritis tersebut.